Bioinformatics and the Cell: Modern Computatioal Approachers in Genomics and Proteomics and Transcriptions - Xuhua Xia (Springer, 2007)
"Bioinformatics and the Cell is the first book with comprehensive numerical illustration of mathematical techniques and computational algorithms used in bioinformatics to convert the rapidly increasing molecular data into organized biological knowledge, with a focus on interactions among DNA, RNA and proteins in the cell. By rendering both mathematics and biology to numbers, this book should appeal not only to biologists, but also to mathematicians, biostatisticians, and computational scientists, especially those younger ones with an ambition to conquer the rough terrain of bioinformatics."